Co-existent B-cell and plasma cell neoplasms: a case series providing novel clinical insight. Issue 3 (3rd March 2016) - Jamani, Kareem; Duggan, Peter; Neri, Paola; Bahlis, Nizar; Jimenez-Zepeda, Victor H.
Abstract : Concomitant plasma cell (PCN) and B-cell neoplasms (BCN) in a single patient have been infrequently reported. This study reviewed nine such patients at the institution – six had multiple myeloma (MM) associated with a BCN (MM/B group) and three had AL amyloidosis (ALA) with a BCN (ALA/B group). This study describes two syndromes of MM/B – three patients presented with CLL and subsequently developed MM, while three presented with MM and monoclonal B-cell lymphocytosis. In the ALA/B group, all three patients had systemic ALA and a BCN. Responses of the BCN and PCN to treatment correlated. In the two patients whose MM relapsed, the BCN simultaneously relapsed. The finding that the BCN may relapse in tandem with the MM argues against a coincidental relationship between the two.